The Relationship Between Knowledge Sharing and Organizational Prosperity: Analytical: Research in The State Company for Electrical and ElectronicIndustries - Reyam Kasim Mohammed, Assistant Prof. Dr. Hadeel Kadhim Saaed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of the research is to investigate the correlation and influence between knowledge sharing and organizational prosperity in the General Company for Electrical and Electronic Industries, and to identify the nature and pattern of thinking prevailing at the different levels in the concerned company, and the extent of its members’ participation with each other ,consolidating the culture of knowledge sharing and directing it towards achieving organizational prosperity.The data was collected from)166(respondents represented by a purposive sample of senior and middle management, and for data analysis, statistical programs were added .SPSS, AMOS )by adopting appropriate statistical methods .The results showed the validity of correlation and influence relationships at the level of the main variables and subdimensions, which indicates the essential role of knowledge sharing to achieve organizational prosperity in the company